2016
DOI: 10.1089/ten.tea.2015.0221
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Stem Cell Fate and Function: A System for Assessing Cell Survival and Collagen ExpressionIn Situ

Abstract: Cell-based therapy is an emerging paradigm in skeletal regenerative medicine. However, the primary means by which transplanted cells contribute to bone repair and regeneration remain controversial. To gain an insight into the mechanisms of how both transplanted and endogenous cells mediate skeletal healing, we used a transgenic mouse strain expressing both the topaz variant of green fluorescent protein under the control of the collagen, type I, alpha 1 promoter/enhancer sequence (Col1a1 GFP ) and membrane-boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
2
7
0
1
Order By: Relevance
“…These results agreed with previous in vitro studies that the BMP‐2 can promote the osteogenic differentiation of transplanted hMSCs (Figures D and ). In addition, it has been found that promoter Col1A1 drove the active expression of type I collagen gene at the early stage of osteoblast differentiation and promoted the extracellular matrix formation and the new bone generation, which was also consistent with the result of our Col1A1–GLuc‐based BLI imaging (Figure ). These results evidenced that the multiplexed imaging method works well in in vivo application.…”
Section: Resultssupporting
confidence: 89%
“…These results agreed with previous in vitro studies that the BMP‐2 can promote the osteogenic differentiation of transplanted hMSCs (Figures D and ). In addition, it has been found that promoter Col1A1 drove the active expression of type I collagen gene at the early stage of osteoblast differentiation and promoted the extracellular matrix formation and the new bone generation, which was also consistent with the result of our Col1A1–GLuc‐based BLI imaging (Figure ). These results evidenced that the multiplexed imaging method works well in in vivo application.…”
Section: Resultssupporting
confidence: 89%
“…For example, pullulan-collagen hydrogel scaffolds seeded with ASCs have been demonstrated to increase vascularity and improve wound healing [ 5 , 6 ]. With regard to skeletal regenerative potential, implantation of an ASC-seeded hydroxyapatite-coated poly (lactic-co-glycolic acid) scaffold into a critical-sized calvarial defect resulted in significant healing of the defect within 8 weeks [ 7 , 8 ]. Finally, the adipogenic and angiogenic capabilities of ASCs have been utilized in the technique of cell-assisted lipotransfer (CAL), in which fat grafts are enriched with their native ASCs to improve retention and variability [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diese heterogene Zellpopulation besteht aus Fibroblasten, Immunzellen, Prä-Adipozyten, Perizyten, Epithelzellen und, am wichtigsten für die regenerativen Eigenschaften, ASCs [7,20]. Die SVF kann entweder direkt zur Zelltherapie eingesetzt [21] oder weiter aufbereitet werden, um in diesem Prozess mittels Zellkultivierung oder Durchflusszytometrie reine ASCs zu gewinnen [22][23][24][25][26]. Ihre therapeutische Wirkung entfalten ASCs durch die Sekretion einer Vielzahl von pro-regenerativen Faktoren, wie pro-angiogenetische und immunmodulierende Zytokine (VEGF, MCP1, etc.…”
Section: Introductionunclassified